Is India Becoming More Liberal? Globalization, Economic Liberalization, and Social Values - Tinaz Pavri (Journal of Global Initiatives, 2018)
India has undergone tremendous change in its economy and polity since its economic liberalization starting in the early 1990s. Globalization and liberalization have, in addition to coinciding with a dramatically increased GDP, increased the presence of global entities and the number of foreign nationals in India, and accelerated the spread of social media. The period has also been marked by a significant increase in xenophobic violence against women, religious minorities and LGBTQ individuals. In light of this sea-change in the country, I examine available survey data on social values of Indians (including young Indians) over the last decade, to see if globalization has also resulted in a change from long-held traditional to progressive global values, particularly on issues of class, gender, caste, religion and LGBTQ issues. I find that the available data indicate mixed trends on these values issues, and offer some explanations as to why that might be the case.